Low load exercise targeting the gluteal muscle group acutely enhance explosive power output in elite athletes - Crow, J. F.; Buttifant, D.; Kearny, S. G.; Hrysomallis, C. (The Journal of Strength and Conditioning Research, 2012)
The purpose of this study was to investigate the acute effect of 3 warm-up protocols on peak power production during countermovement jump (CMJ) testing. The intention was to devise and compare practical protocols that could be applied as a warm-up immediately before competition matches or weight training sessions. A group of 22 elite Australian Rules Football players performed 3 different warm-up protocols over 3 testing sessions in a randomized order. The protocols included a series of low load exercises targeting the gluteal muscle group (GM-P), a whole-body vibration (WBV) protocol (WBV-P) wherein the subjects stood on a platform vibrating at 30 Hz for 45 seconds, and a no-warm-up condition (CON). The CMJ testing was performed within 5 minutes of each warm-up protocol on an unloaded Smith machine using a linear encoder to measure peak power output. Peak power production was significantly greater after the GM-P than after both the CON (p < 0.05) and WBV-P (p < 0.01). No significant differences in peak power production were detected between the WBV-P and CON. These results have demonstrated that a low load exercise protocol targeting the gluteal muscle group is effective at acutely enhancing peak power output in elite athletes. The mechanisms for the observed improvements are unclear and warrant further investigation. Coaches may consider incorporating low load exercises targeting the gluteal muscle group into the warm-up of athletes competing in sports requiring explosive power output of the lower limbs.